Jews and Germans in Hamburg: the destruction of a civilization 1790 - 1945 - Grenville, John A. S. (Routledge, 2012)
Last days in Hamburg -- Earlier times -- The shadow of the Nazis -- How will it end? -- Courage in adversity -- Yourself, if you can -- Holocaust -- Refelections